2017
DOI: 10.1161/circoutcomes.117.003616
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Primary Noncardiac Diagnoses Over Time Among Elderly Cardiac Intensive Care Unit Patients in the United States

Abstract: Background Early reports suggest the number of CICU patients with primary non-cardiac diagnoses is rising in the U.S., but no national data currently exist. We examined changes in primary non-cardiac diagnoses among elderly patients admitted to a cardiac intensive care unit (CICU) over the last decade. Methods and Results Using 2003–2013 Medicare data, we grouped elderly patients admitted to CICUs into two categories based on principal diagnosis at discharge: 1) primary non-cardiac diagnoses and 2) primary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 28 publications
3
62
1
Order By: Relevance
“…Consequently, these patients may suffer a larger clinically meaningful impact of short-term PM 2.5 exposure that is not limited to the cardiovascular system. On the other hand, some studies have reported that ANCI is common and associates with increased mortality risk in contemporary ICCU settings (9,10). In consideration of a possible multisystemic consequence following short-term PM 2.5 exposure and the meaningfulness of ANCI, it is crucial to explore whether short-term PM 2.5 exposure is associated with the incidence of major ANCI.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, these patients may suffer a larger clinically meaningful impact of short-term PM 2.5 exposure that is not limited to the cardiovascular system. On the other hand, some studies have reported that ANCI is common and associates with increased mortality risk in contemporary ICCU settings (9,10). In consideration of a possible multisystemic consequence following short-term PM 2.5 exposure and the meaningfulness of ANCI, it is crucial to explore whether short-term PM 2.5 exposure is associated with the incidence of major ANCI.…”
Section: Discussionmentioning
confidence: 99%
“…There are inherent differences between patients admitted to different specialty units on admission diagnoses, nosocomial infection rates, and mortality. (3335) Unfortunately, we are unable to identify medical patients who were boarded in non-medical ICUs as this may have an impact on mortality. Finally, while the MIMIC-III database is a large, granular, ICU database; it is a single center database.…”
Section: Discussionmentioning
confidence: 99%
“…7 CICU-specific revenue center codes within the claim records identified hospitalizations with a CICU stay. The principal finding of Sinha et al was a remarkable increase in the proportion of noncardiac primary diagnoses from 38.0% to 51.7% with a concurrent decline in primary diagnoses related to coronary artery disease from 32.3% to 19.0%.…”
Section: Transformation Of the Cicumentioning
confidence: 99%
“…7 By 2013, renal replacement therapy exceeded the use of pulmonary artery catheters and mechanical circulatory support combined. Patients with noncardiac primary diagnoses had more than double the rate of positive pressure ventilation and nearly double the rate of hemodialysis.…”
Section: Morrow Trends In Cardiac Critical Carementioning
confidence: 99%
See 1 more Smart Citation